Legumes of the Great Plains : An Illustrated Guide - Stubbendieck, James L.; Milby, Jessica L. (Book collections on Project MUSE., 2021)
This comprehensive guide of legumes of the Great Plains includes an in-depth description of 114 species with illustrations and distribution maps. It includes more than one hundred similar species with a description of how each differs from the main species.